THE ENVIRONMENTAL IMPACT OF NATURE BASED TOURISM IN GUNUNG MERAPI NATIONAL PARK - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The goal of this research is to find out some impacts of tourism activities to the environmental mainly to the biotic and non-biotic components. The research also focuses in finding out importance and performance of the products offered-by Gunung Merapi National Park to the tourists. This research is done in four locations, consisted of the undisturbed location for controlling (Plawangan) and the disturbed locations caused by the tourists, which are Kalikuning, Tlogonirmolo and Tlogomuncar. The result shows that the impClcts of tourist activities in some locations show that the number of .microbial in the controlling location-is the highest (54.56 cfu/gram) compared with others location. The impact to the number of actin0mycetes in the controlling location is 32.84 cfu/gram, which is the highest. The infiltration rate with the model Horton in the controlling location is higher (0.983 cm/min) than the infiltration rates of the others. The voice frequency describes crowd level that at the controlling location has the lowest voice frequency (10.15 dB). Some kinds of tree destruction as the impact of tourist activities show that the destructions happen mostly in Tlogomuncar, followed with Kalikuning and Tlogonirmo 10. The most severe destruction of all locations is vandalism, and then scratch, spike prickling, branch breaking, and waste burning. Ihe importance and .performance of the products of the tourism objects offered describe that the attractions and tourism facilities like waterfall, musholla, shelter, dustbin, and observer tower have a considerable perception and good performance. However, some other facilities/attractions such as operational office, security center, gate, health clinique and bridge are not very important and not in a good condition.